Evaluating the performance of a web-based vehicle blind zone estimation application: Validation and policy implications - Drake, Juwon; Vennema, Alessandra; Slonim, Lily; Englin, Eric; Brodeur, Alyssa; Epstein, Alexander K.; Fisher, Donald L. (Frontiers in Future Transportation, 2023)
Pedestrian fatalities have been increasing in the United States over the past decade: in 2021 they reached a 40-year high (Macek, 2022), and together with an increasing number of bicyclist fatalities surged to over 8,400 vulnerable road users (VRUs) killed by motor vehicle crashes. There is widespread recognition of the link between passenger fleets transitioning from sedans to SUVs and pick-up trucks (Federal Reserve, 2022) and the increase in vulnerable road user fatalities (Auffhammer, 2014). Larger light-duty vehicles generally have larger blind zones, which are prominently linked to crashes with VRUs. Heavy-duty commercial trucks, which comprise only four percent of vehicles on the road, are disproportionally associated with over eight percent of VRU deaths. (NHTSA, 2022) With direct vision unregulated in the United States, there is a limited domestic market for large trucks with high direct vision despite research showing that one-quarter of the approximately 640 annual truck-involved pedestrian and bicyclist fatalities result from low-speed maneuvers with impaired direct vision and could be prevented by higher vision truck cabs. (Blower, 2006) Communicating the seriousness of this problem is critical. This Methods article presents an easy-to-use tool designed to give the public and fleet managers information to assess the vehicle safety by quantifying driver blind zones. Previously, measures of the percentage of volume surrounding the vehicle that cannot be seen could only be made with specialized instrumentation. The web-based application described, VIEW or Visibility in Elevated Wide Vehicles, can be used by anyone with a camera and access to the internet to obtain within minutes a reasonably accurate measure of the blind zone size. This article details the app usage procedure as well as the validation work conducted. The app estimates that eight elementary school children can stand in a line in front of a Chevrolet Silverado, the third most sold pick-up truck in the U.S., and not be visible to the driver. In summary, the safety culture around SUVs, pickup trucks, and heavy-duty commercial trucks may well change if drivers had an easy-to-use method to determine how much situational awareness they would be missing before they purchased a particular vehicle.